Comprehensive study of the thermo-reversibility of Diels–Alder based PCL polymer networks. (10th February 2016) - Defize, Thomas; Thomassin, Jean-Michel; Alexandre, Michaël; Gilbert, Bernard; Riva, Raphaël; Jérôme, Christine
Abstract: Chemical crosslinking is an efficient tool to improve or impart new properties to conventional polymers. Especially, crosslinking imparts remarkable shape–memory properties to poly-ε-caprolactone (PCL) materials. Nevertheless, the processing of networks is often tricky due to infusibility and insolubility of cross-linked chains. Therefore, the synthesis of PCL networks including thermo-reversible crosslinks based on (retro)-Diels-Alder (DA) reaction were developed to allow preserving the melt-processing while keeping the required mechanical properties below the melting point. This paper aims at studying in depth, such thermo-dependent network formation and stability. Besides conventional swelling experiments, Raman spectroscopy was revealed as a powerful tool to follow the formation of the DA adduct during the crosslinking. In combination with rheological measurements, we were able to determine the most appropriate temperatures to form the network (DA crosslinking) and to process it (retro-DA reaction) without degradation of the material. Graphical abstract: Highlights: Quantification of the Diels–Alder reaction yield by Raman spectroscopy. Determination of optimal temperatures of crosslinking and reprocessing by rheology. Investigation of thermoreversibility by Raman spectroscopy and rheology.